2020
DOI: 10.1055/s-0040-1721851
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene-Based Diarynes as Precursors for Twisted Fused Polycyclic Aromatic Hydrocarbons: A Comparison of Two Routes

Abstract: Two bench-stable and readily accessible pyrene-based diaryne precursors based on triflate as well as TMS triflate motifs are introduced and compared in their [4+2]-Diels–Alder reactions with tetracyclone to give an oligophenyl-substituted dibenzo[e,l]pyrene in both cases. By single-crystal X-ray analysis, this twistacene showed helical chirality and an end-to-end contortion of 49.6° due to steric repulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Crystal structure of compound 2HH has been reported, and belonged to the orthorhombic system with an Fddd space group [33] . However, we obtained a crystal of compound 2HH in the monoclinic crystal system, which was assigned to the C2/c space group (Figure 6).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Crystal structure of compound 2HH has been reported, and belonged to the orthorhombic system with an Fddd space group [33] . However, we obtained a crystal of compound 2HH in the monoclinic crystal system, which was assigned to the C2/c space group (Figure 6).…”
Section: Resultsmentioning
confidence: 87%
“…Crystal structure of compound 2HH has been reported, and belonged to the orthorhombic system with an Fddd space group. [33] However, we obtained a crystal of compound 2HH in the monoclinic crystal system, which was assigned to the C2/c space group (Figure 6). In the crystal structure of 2HH, each molecule was connected through one type (2 numbers) of CÀ H•••π interactions between the π clouds of the pyrene units and the hydrogen atoms in the unsubstituted aromatic ring of the adjacent molecule, with a distance of 2.55 Å.…”
Section: Single-crystal Structuresmentioning
confidence: 99%
“…37 Lately, eight phenyl substituted dibenzo[e, l]pyrene (V) by Mastalerz et al showed the helical structure with an end-to-end twist of 49.6°. 38 Recently, we introduced [n]helicene as a strain-inducing tensor for generating twisted acene core within a pyrene-fused [n]helicene moiety, achieving end-to-end twist of 50°by incorporating methyl substituted [5]helicene at the K-region of pyrene (VI) and a 44°end-to-end twist upon using [7]helicene (VII). [39][40][41] The helicity of twisted core was dictated by the helicity of the attached [n]helicene, which was opposite to each other.…”
Section: Introductionmentioning
confidence: 99%
“…During our research on using di‐ tert ‐butylpyrene TMS‐triflates for PAH synthesis, [14c] we found by MALDI‐TOF mass spectrometric analysis of the crude product of structurally related mono aryne precursor 1 in Pd‐catalyzed reactions besides the expected trimer unprecedented larger oligomers have formed (Figure 1). Despite the vast number of PAHs having synthesized by this method and their in‐depth analyses both, theoretically and experimentally, the formation of higher oligomers has to the best of our knowledge not been reported.…”
Section: Introductionmentioning
confidence: 99%